2019
DOI: 10.1371/journal.pone.0212449
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis finds differences on the muscle transcriptome of pigs fed an n-3 PUFA-enriched diet with or without antioxidant supplementations

Abstract: Supplementing pig diets with n -3 polyunsaturated fatty acids ( n- 3 PUFA) may produce meat products with an increased n -3 fatty acid content, and the combined antioxidants addition could prevent lipid oxidation in the feed. However, to date, the effects of these bioactive compounds at the molecular level in porcine skeletal muscle are mostly unknown. This study aimed to analyse changes in the Longissimus thoracis tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 85 publications
1
10
0
1
Order By: Relevance
“…This could be due to different effects of diets enriched with n-3 PUFA and natural or synthetic antioxidants in modulating the expression of pig skeletal muscle genes involved in de novo synthesis of FA and metabolism of lipids. Vitali et al (2019) reported a more evident stimulation of the expression of genes involved in controlling muscle metabolism when n-3 dietary PUFA are administered in association with polyphenols-enriched diet.…”
Section: Raw and Cooked Meat Characteristicsmentioning
confidence: 99%
“…This could be due to different effects of diets enriched with n-3 PUFA and natural or synthetic antioxidants in modulating the expression of pig skeletal muscle genes involved in de novo synthesis of FA and metabolism of lipids. Vitali et al (2019) reported a more evident stimulation of the expression of genes involved in controlling muscle metabolism when n-3 dietary PUFA are administered in association with polyphenols-enriched diet.…”
Section: Raw and Cooked Meat Characteristicsmentioning
confidence: 99%
“…The diet with additional polyphenols seemed to have a major effect on genes involved in muscle development, as the expression of genes associated with lipid metabolism and immune system was increased (Sirri et al 2018). These observations were confirmed in a later study by the same research group (Vitali et al 2019). Recently, the yeast-derived mannan-rich fraction was tested in piglets (Fouhse et al 2019); the mannan is considered an antioxidant and an antiproliferative polysaccharide that plays a protective role against gastrointestinal infections.…”
Section: Supplementation With Vitamins and Mineralsmentioning
confidence: 74%
“…So far, to the best of our knowledge very few, if any (e.g., in rats (Zhou et al, 2019), in pigs (Vitali et al, 2019)), studies have analyzed bovine muscle transcriptomes in response to treatment with RSV. Therefore, the aim of this study was to conduct a genome-wide transcriptome study on beef skeletal muscle cells in the absence and presence of RSV to reveal differentially expressed genes.…”
Section: Introductionmentioning
confidence: 99%